2020
DOI: 10.1044/2020_jslhr-19-00114
|View full text |Cite
|
Sign up to set email alerts
|

Age Norms for Auditory-Perceptual Neurophonetic Parameters: A Prerequisite for the Assessment of Childhood Dysarthria

Abstract: Purpose The aim of this study was to collect auditory-perceptual data on established symptom categories of dysarthria from typically developing children between 3 and 9 years of age, for the purpose of creating age norms for dysarthria assessment. Method One hundred forty-four typically developing children (3;0–9;11 [years;months], 72 girls and 72 boys) participated. We used a computer-based game specifically designed for this study to elicit sentence r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 39 publications
2
26
0
3
Order By: Relevance
“…The ratings were completed by either TS or EH, who were blind for the motor type of CP at the time of the speech evaluation. For details of construction, reliability, and validity of the original BoDyS protocol see Ziegler et al, 25 and for analyses of interrater reliability in children see Schölderle et al 21 In the variables chosen as classifiers, the observed frequency of occurrence of a feature was weighted by the severity score of its corresponding scale, using the formula:: 4 À ðrelative frequency of occurrence  4 À mean score on corresponding scale ½ Þ :…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The ratings were completed by either TS or EH, who were blind for the motor type of CP at the time of the speech evaluation. For details of construction, reliability, and validity of the original BoDyS protocol see Ziegler et al, 25 and for analyses of interrater reliability in children see Schölderle et al 21 In the variables chosen as classifiers, the observed frequency of occurrence of a feature was weighted by the severity score of its corresponding scale, using the formula:: 4 À ðrelative frequency of occurrence  4 À mean score on corresponding scale ½ Þ :…”
Section: Assessmentmentioning
confidence: 99%
“…For example, the articulation rate scale comprises the two features reduced rate and increased rate, and the voice quality scale comprises the features breathy voice, strained-strangled voice, rough/harsh voice, and fluctuating voice quality. 21,25 Following the original BoDyS protocol, we documented the presence of each feature in each speech sample, from which we calculated the relative frequency of occurrence (ranging from 0=not observed to 1=observed in each of the six samples). The nine scales were rated for severity on a five-point equal-appearing interval scale (0=very severe; 4=no disorder) for each speech sample separately.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Die typisch entwickelten Kinder wurden zur Erhebung auditiver Normdaten untersucht (vgl. [14]). Alle Kinder waren muttersprachlich deutsch, wiesen keine organischen Erkrankungen der Atemwege oder Sprechorgane und keine Hörstörungen auf.…”
Section: Praktikabilitätsnachweisunclassified
“…Das Untersuchungsmaterial stellt somit die Basis für eine gezielte auditive Analyse dysarthrischer Störungen bei Kindern dar. Dazu liegen altersbezogene Normdaten für 3-bis 9-Jährige vor [14], die in Zukunft für Kinder bis ins Alter der Pubertät ausgeweitet werden sollen.…”
Section: Klinische Implikationenunclassified